Milton's peculiar grace : self-representation and authority - Fallon, Stephen M. (Book collections on Project MUSE., 2007)
"In Milton's Peculiar Grace, Fallon argues that Milton writes about himself to gain immortality, secure authority for his arguments, and exert control over his readers' interpretations. He traces the return of the repressed narrative of fallenness in the author's unacknowledged and displaced self-representations, which in turn account for much of the power of the late poems. Fallon's book, based on close readings of Milton's "self-constructions" in prose and poetry throughout his career, provides a new view of Milton's life and his importance for contemporary literary theory - in particular for continued questions about authorial intention."--Jacket